Effectiveness of Technology-Based Flipbook Media in Enhancing Learning Motivation in Social Studies for Grade XI Students - Dilla Sylvia; Ponidi Ponidi (MASI Mandiri Edukasi, 2025)
This study aims to describe the effectiveness of using technology-based Flipbook learning media in increasing students' learning motivation in Social Studies (IPS) subjects in grade XI at SMAS Dharma Utama Medan. The background of the research stems from the low motivation and participation of students in IPS learning, which is still dominated by conventional methods. This study uses a qualitative approach with a case study design to gain an in-depth understanding of students' learning experiences using Flipbooks. The research subjects consisted of IPS teachers and eighth grade XI students, while data were collected through observations, in-depth interviews, and documentation during the period from July to September 2025. The research results indicate a substantial increase in students' motivation and engagement following the implementation of Flipbook media. Students became more active in discussions, were bolder in asking questions, and showed higher interest and learning independence. The use of a Flipbook with text, image, video, and interactive animation features created an engaging and enjoyable learning environment, thereby fostering students' intrinsic motivation to understand social studies material independently. Additionally, Flipbook-based learning also strengthened digital literacy and increased students' active participation in the learning process.